Real‐time predictive coordination based on vehicle‐triggered platoon dispersion in a low penetration connected vehicle environment - Jiangchen Li (Wiley, 2021)
Abstract The connected vehicle (CV) technology can benefit signal coordination with fine‐grained spatial and temporal vehicle and infrastructure data via real‐time communication. Although CV‐based signal coordination systems have been investigated from offline and online strategic perspectives, existing works have yet to address certain coordination performance issues, including the dynamic platoon dispersion effect and low penetration impact. Targeting at resolving these issues, this work proposes a real‐time predictive coordination method consisting of a probabilistic single‐vehicle‐based dynamic platoon dispersion model, an extended link performance function, and a real‐time model predictive control (MPC)‐based coordination framework. The proposed coordination method was comprehensively investigated by a software‐in‐loop simulation platform with different practical corridor scenarios in the ACTIVE CV testbed in Canada. Results show the proposed coordination control continuously outperformed existing signal control with lower delays for major streets with different demand profiles and different CV penetration rates, even in low penetration conditions. In conclusion, the proposed CV MPC‐based coordination can offer significant potential to further improve the system performance of signal coordination in a low penetration environment; therefore, it has the potential to enhance other CV‐based signal control applications in the initial deployment stage of CV technology.